Luật lệ về tư pháp, theo các văn bàn đã công bố năm . (Vietnamese law coll. (Harvard Law School), 1963)
Laws and regulations on judicial organization, democratic freedoms, criminal law, civil law, marriage and family, procedural law and a number of important policies, including legal education and propagandas covering from 1945 to 1967.